2020
DOI: 10.3389/fphar.2019.01565
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rg1 as an Effective Regulator of Mesenchymal Stem Cells

Abstract: Recently, breakthroughs have been made in the use of mesenchymal stem cells (MSCs) to treat various diseases. Several stem cell types have been authorized as drugs by the European Medicines Agency and the U.S. Food and Drug Administration. The Chinese official document "Notification of the management of stem cell clinical research (trial)" was also published in August 2015. Currently, China has approved 106 official stem cell clinical research filing agencies and 62 clinical research projects, which are mostly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 112 publications
1
30
0
Order By: Relevance
“…Among the various ginsenosides, Rg1 is a tetracyclic triterpenoid monomer. Rg1 has been known to affect various human organ systems including the immune, cardiovascular, and nervous systems with its pharmacological effects [ 7 ]. Notably, Rg1 reduces apoptosis of nerve cells and exerts protective effects on neurons [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the various ginsenosides, Rg1 is a tetracyclic triterpenoid monomer. Rg1 has been known to affect various human organ systems including the immune, cardiovascular, and nervous systems with its pharmacological effects [ 7 ]. Notably, Rg1 reduces apoptosis of nerve cells and exerts protective effects on neurons [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rg1 shows pharmacological effects in various organ systems such as the nervous and immune systems [4,5]. It is particularly known to reduce apoptosis of nerve cells and mesenchymal stem cells [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Other in vivo experiments also reported that Rg1 stimulates the myocardial tissue secretion of granulocyte colony-stimulating factor (G-CSF), able to promotes BMSC homing to myocardial tissue and differentiation into vascular endothelial cells. Interestingly, a reduction in the size of the myocardial infarction and an improvement in cardiac function were observed in this condition [ 242 ]. In a rat model of acute MI it was also observed how the continuous application of Rg1 enhances the number of peripheral blood CD34 + stem cells and stimulates the homing of stem cells to the infarcted area, leading to ventricular remodeling with reduction of infarct size and significant myocardial regeneration [ 243 ].…”
Section: Natural Compounds and Stem Cells Activation And Differentmentioning
confidence: 99%
“…Phytochemicals possess the ability to induce apoptosis through the generation of ROS in breast cancer cells [ 11 ]. Ginsenoside Rg1 is the primary active component of Panax ginseng which has been endowed with several pharmacological properties [ 12 ]. Ginsenoside Rg1 is derived from a hydride of a dammarane and is a monomer of a tetracyclic triterpenoid derivative [ 13 ].…”
Section: Introductionmentioning
confidence: 99%